Improving Junior High School students' vocabulary achievement by using WhatsApp - Toni, Atrianus (Journal of English Language and Pedagogy (JELPA), 2023)
Mobile messaging applications are increasingly widespread among the new generation of students in Indonesia. They use michat, line, WhatsApp and the other messaging applications. This study aimed to improve students' vocabulary achievement by using WhatsApp of VII C students of SMPS Panca Setya Sintang in the academic year 2022/2023. In one cycle, the writer used classroom action research on 19 male and 11 female students. The writer sent vocabulary instructions electronically for two meetings. The multiple-choice test was conducted after each meeting. The results showed that 63,33 % of the students could improve their achievement in the second meeting. It means that the use of WhatsApp in teaching vocabulary can improve students' achievement. Referring to the writer's experience in conducting action research, the writer offers a suggestion. It is suggested that English teachers can use WhatsApp as an alternative application to improve students' vocabulary achievement.